Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan pada Rumah Makan Nasi Liwet Cipancar - Abdurohman, Abdurohman; Adji, Widwi Handari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
service and product quality on consumer satisfaction at Nasi Liwet Cipancar Restaurant. As many as 99 respondents for the sample taken using the Non-Probability sampling technique with the Accidential sampling approach. So that there is a simultaneous influence between variable X1 and variable X2 on Y with SPSS V.26 of 56% and the remaining 43.4% is attributed to other factors that were not examined in this research. Keywords: Service Quality, Product Quality, Customer Satisfaction